Simultaneous inhibition of IGF1R and EGFR enhances the efficacy of standard treatment for colorectal cancer by the impairment of DNA repair and the induction of cell death. (28th October 2017) - Oberthür, Rabea; Seemann, Henning; Gehrig, Julia; Rave-Fränk, Margret; Bremmer, Felix; Halpape, Rovena; Conradi, Lena-Christin; Scharf, Jens-Gerd; Burfeind, Peter; Kaulfuß, Silke
Abstract: Overexpression and activation of receptor tyrosine kinases (RTKs), such as the insulin-like growth factor 1 receptor (IGF1R) and the epidermal growth factor receptor (EGFR), are frequent phenomena in colorectal cancer (CRC). Here, we evaluated the effect and the cellular mechanisms of the simultaneous inhibition of these two RTKs both in vitro and in vivo in addition to a 5-fluoruracil (5-FU)-based radiochemotherapy (RCT), which is a standard treatment scheme for CRC. Using the small molecule inhibitors AEW541 and erlotinib, specific against IGF1R and EGFR, respectively, different CRC cell lines exhibited a reduced survival fraction after RCT, with the highest effect after the simultaneous inhibition of IGF1R/EGFR. In vivo, xenograft mice simultaneously treated with low dose AEW541/erlotinib plus RCT revealed a significant reduction in tumour volume and weight compared with the tumours of mice treated with either AEW541 or erlotinib alone. In vitro, the combined inhibition of IGF1R/EGFR resulted in a stronger reduction of downstream signalling, an increase in DNA double strand breaks (DSBs), apoptosis and mitotic catastrophe after RCT depending on the cell line. Moreover, the existence of IGF1R/EGFR heterodimers in CRC cells and human rectal cancer samples was proven. The heterodimerisation of these RTKs was dependent on the presence of both ligands, IGF-1 and EGF, and functional receptors. In conclusion, these results demonstrate that the strategy of targeting both IGF1R and EGFR, in addition to basic RCT, could be of intriguing importance in CRC therapy. Highlights: Simultaneous inhibition of IGF1R/EGFR enhances standard radiochemotherapy in CRC. Low dose IGF1R/EGFR inhibition reduces tumour growth in vivo / in vitro . IGF1R/EGFR inhibition leads to diminished downstream signalling and DNA repair. CRC cell lines undergo apoptosis and mitotic catastrophe. IGF1R and EGFR form heterodimers in CRC cell lines and human rectal cancer samples.